Exchange-rate devaluation in a semi-industrialized country : the experience of Argentina 1955-1961 - Diaz-Alejandro, C.F. (Cambridge ; Massachausetts ; London : The M.I.T. Press, 1965)
The purpose of this study is to analyze the impact of devaluation of the exchange rate on the Argentine economy and the balance of payments.
Includes bibliographical references and index
osc 22/2/17
Loans
Keywords: Foreign Exchange; Monetary policy; Balance of trade; Economic history; Devaluation of currency; Foreign exchange rates; Argentina